2013
DOI: 10.4236/ojpsych.2013.32019
|View full text |Cite
|
Sign up to set email alerts
|

A neuropsychological evaluation of orthorexia nervosa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
4
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 44 publications
5
76
4
8
Order By: Relevance
“…One prediction suggests that, for example, that like other eating disorders, ON may be characterized by the inability to adapt thinking to newly encountered information/events. This cognitive inflexibility, however, was not shown to be characteristic of ON compared to controls [16,32].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…One prediction suggests that, for example, that like other eating disorders, ON may be characterized by the inability to adapt thinking to newly encountered information/events. This cognitive inflexibility, however, was not shown to be characteristic of ON compared to controls [16,32].…”
Section: Introductionmentioning
confidence: 58%
“…Whilst it has been argued that ON is a unique and specific eating disorder [12,15,16], a number of studies have identified common affective and cognitive agents operating in ON, obsessive-compulsive disorder (OCD) and other eating disorders [17,18]. More specifically, it has been suggested that anxious states similar to those reported by people with anorexia nervosa (AN) and OCD (strong beliefs about food and obsessive eating habits) may be characteristic of ON [19,20] and lead to "health anxiety" [21].…”
Section: Introductionmentioning
confidence: 99%
“…abrytek-matera@swps.edu.pl ON usually starts as a health concern followed by efforts to achieve optimum health through diet but it leads to significant damages up to malnutrition, impaired social life, and quality of life deterioration [10]. Diet becomes the main part of people's thoughts and concerns [2] leading to distress about eating with significant dietary restrictions and consequent loss of food enjoyment, co-occurrence of anxiety with the need of control over food intake [12], rigid/inflexible eating behaviors and ritual meal preparation [11,20] desiring to achieve self-esteem and self-realization through control of food intake [21]. Sometimes this may be associated with unintentional weight loss, apparently with no desire to lose weight rather subordinated to ideation about healthy food.…”
Section: And Anna Brytek-materamentioning
confidence: 99%
“…The study by Brytek-Matera et al [26] suggested that orthorexic behaviors were associated with an unhealthy or negative body image among students although their strong concern about healthy and appropriate food choices. The most recent diagnostic criteria acknowledge obsessive-compulsive behavior, as previously reviewed by Koven and Abry [10] and demonstrated by Koven and Senbonmatsu [20]. As for obsessive-compulsive disorder, even orthorexia nervosa is characterized by the occurrence of persistent obsession (e.g.…”
Section: And Anna Brytek-materamentioning
confidence: 99%
See 1 more Smart Citation